Correlations for the sulfur contents of Turkish coals exposed to ashing and devolatilization conditions at 750 degrees C and 950 degrees C - (:unkn) unknown (ELSEVIER SCI LTD, 1998)
Total sulfur, sulfur forms, CaO, MgO and ash were analyzed in 19 selected Turkish coals with widely varying characteristics (from bituminous coal to low grade lignite) according to the American Society for Testing and Materials (ASTM) standards. The combustible sulfur contents of coals, the sulfur retained in the coal ash, the volatile sulfur content, and the sulfur retained in the coal char (the non volatile sulfur content) were determined at two different temperatures, namely 750 degrees C and 950 degrees C. Formulae were developed to correlate the before-mentioned coal properties with the combustible sulfur and char sulfur contents of coals at 750 degrees C and 950 degrees C. Correlations based on the sulfur forms and CaO and MgO contents gave the least erroneous results. (C) 1998 Elsevier Science Ltd All rights reserved.
Keywords: combustible sulfur; volatile sulfur; non-volatile sulfur; sulfur in char; correlations; FLUIDIZED-BED COMBUSTOR; LOW-RANK COAL; PYROLYSIS; RETENTION; OXIDATION; CHEMISTRY; LIGNITES; PRODUCTS; PYRITE; FORMS